SIGNIFICANT WASTE FACTORS INFLUENCING DELIVERY COST PERFORMANCE OF DESIGN AND BUILD LOW COST HOUSING PROJECTS IN IMO STATE NIGERIA - Lovelin OBI; Mohammed ARIF; Bankole AWUZIE (Journal of Construction Project Management and Innovation)
Effective performances particularly on Low cost housing projects has been a major problem in many developing countries. In Nigeria public sector clients have adopted the design and build (DB) procurement strategy as one of the strategies to deliver Low cost housing (LcH) projects following potential benefits to facilitate improved performances particularly as it pertains to project cost Yet, many design and build low cost housing ( projects are not delivered within expected tar get cost performances resulting from the influences of waste factors amongst several others identified Th is paper aim to identify the waste factors that significantly influence poor cost performances of DBLcH projects based on the investigation of the LcH sector in Imo S tate Nigeria. A mixed method design , using literature review and survey questionnaire, was adopted in this study to identify and validate contextual waste factors influencing DBLc H project cost performances. Findings revealed the significant waste factors influencing poor cost performances of DBLcH projects . This study ’s findings is expected to increase the awareness of the p roject team on the significant waste factors that will need to be mitigated towards improving the cost performances of DBLcH projects in Imo S tate Nigeria